Pengelolaan Food Loss dan Food Waste Melalui Kemitraan Berbasis Komunitas Di Provinsi Lampung (Studi Kasus Komunitas Ruang Pangan) - Purwadi, Yustina; Tresiana, Novita; Faedlulloh, Dodi (Jurusan Ilmu Administrasi Publik FISIP Universitas Lampung, 2025)
Food Loss and Waste (FLW) is a significant global issue, contributing approximately 8-10% of global greenhouse gas emissions. The lack of well-structured and effective waste management systems is one of the causes of high waste generation, particularly in Lampung Province. This study aims to analyze the governance practices of the Ruang Pangan Community in managing FLW in Lampung Province, as well as the obstacles encountered in the process. This research employs a descriptive qualitative method using Ansell and Gash’s collaborative governance theory approach. The results indicate that the governance of the Ruang Pangan Community, when examined through the lens of Thomson and Perry’s collaborative approach, remains at the cooperation stage. Although the elements of collaboration are fulfilled, the process is still autonomous, where each actor operates within their respective roles without deep structural integration, and there are still dominant actors in the FLW management process. The primary obstacles faced by the Ruang Pangan Community include low public awareness regarding the importance of FLW management, despite its critical impacts. Therefore, appropriate regulations and programs are urgently needed to address this issue effectively.